The relationship between latitudinal light variation and orbit and cranial size in humans - Short, Alice (Anthropological Review, 2016)
Increased orbit size is suggested to be an adaptation for enhanced visual acuity and sensitivity in conditions of reduced light quality. Whilst light ambience has a well established correlation with eye size in birds and primates, evidence in humans is very limited. The aim of this study was to analyse the anatomical compensations of the eye and visual cortex as a result of varying levels of light exposure. It was hypothesized that humans of higher latitudes will have an increased orbit size to improve visual sensitivity and acuity in conditions of decreased light, and thus greater cranium size due to enlarged visual cortices. Craniometric measurements of 1,209 male and 1,021 female individuals from 27 series coming from different latitudes were sourced from William W. Howells Craniometric Data Set. Mean cranial and orbit size was calculated by combining linear craniometric measurements of length, width and height for individual males and females at each latitude. Linear regressions of orbit and cranial size on latitude were created and significance was measured using Pearson’s r and P value. Partial correlations were calculated to test whether orbit size correlates with latitude independent of cranial size. Significant positive correlations were found between i) orbit and cranial size and ii) orbit size and latitude and iii) cranial size and latitude in males and females. Additionally, partial correlation values for latitude and orbit size were significant in both males and females. The relationship between visual system size and increasing latitude among humans is currently understudied. Significant relationships between visual system size and increasing latitude suggest that enlarged eyes were an evolutionary mechanism for individuals with compromised light availability. Other factors related to varying geographic location may also play a role.